Efficacy and Safety of Tripterygium Wilfordii Glycoside Tablets Combined with Acitretin Capsules in the Treatment of Moderate to Severe Plaque Psoriasis: A Randomized Controlled Trial - Qinghui Fu; Yunjie Zhu; Yiqi Fang; Changbo Dai (Applied Bionics and Biomechanics)
Objective. To probe into the clinical efficacy of tripterygium wilfordii glycoside (TWGs) tablets combined with acitretin capsules in the treatment of patients with moderate to severe plaque psoriasis (MSPP). Methods. Thirty-six patients with MSPP were collected and divided into three groups, namely, group A (n=12, TWG tablets + acitretin capsules), group B (n=12, compound glycyrrhizin capsules + acitretin capsules), and group C (n=12, acitretin capsules). The general data of the patients was recorded. In addition, a comparison was made before treatment, 4 weeks and 8 weeks after treatment in terms of the clinical efficacy, liver function indicators (alanine aminotransferase (ALT), aspartate transaminase (AST), and creatinine), psoriasis area, and severity index (PASI) scores. The incidence of adverse reactions after treatment and the recurrence rate during two months of follow-up was statistically analyzed. Results. The therapeutic effect of group A was superior to the other two groups, with obviously more satisfactory results of serum parameters, clinical efficacy and PASI score, and incidence of adverse reactions. Conclusions. TWGs combined with acitretin had better therapeutic effects and higher safety in the treatment of MSPP.